Are medication effects on subjective response to alcohol and cue-induced craving associated? A meta regression study. - Ray, Lara A.; Nieto, Steven J.; Meredith, Lindsay R.; Burnette, Elizabeth; Donato, Suzanna; Magill, Molly; Du, Han (Psychopharmacology, 2023)
Rationale: Alcohol administration and cue-reactivity paradigms are frequently used to screen for the initial efficacy of medications for alcohol use disorder (AUD). While medication effects on the primary outcomes for these paradigms are assumed to be qualitatively related, there is a critical lack of quantitative evidence to support this hypothesis. Objectives: The study aims to test the relationship between medication effect sizes on subjective response to alcohol administration and medication effect sizes for cue-induced craving to cue exposure, using meta-analysis. Methods: Systematic literature searches were conducted to identify randomized trials, wherein AUD medications were tested using the alcohol administration and/or cue-reactivity paradigms. From these studies, descriptive statistics were collected to compute medication effect sizes on the primary outcomes for each respective paradigm. With medication as the unit of analysis, medication effect sizes in alcohol administration studies were compared with medication effect sizes in cue-reactivity studies using the Williamson-York regression which allows for meta-regression across independent samples. Results: Medication effect sizes on alcohol-induced stimulation and alcohol-induced craving were not significantly associated with medication effect sizes on cue-induced alcohol craving (k stimulation = 10 medications, β ^ = 0.272 SE = 0.263 , p = 0.150 and k craving = 11 medications, β ^ = 0.217 (SE = 0.237), p = 0.181 ), respectively. Medication effect sizes on alcohol-induced sedation were significantly associated with medication effects on cue-induced craving (k = 10 medications, β ^ = - 0.600 (SE = 0.258), p = 0.010 ), such that medications that increased alcohol-induced sedation were more likely to reduce cue-induced alcohol craving. Conclusions: With the exception of alcohol-induced sedation, there is little quantitative evidence of medication effects on subjective response domains measured during alcohol administration parallel medication effects on cue-induced alcohol craving. To provide additional context to the current study, future work should examine whether cue-reactivity findings predict clinical trial outcomes.